The Oxidative State of Chylomicron Remnants Influences Their Modulation of Human Monocyte Activation - Sandra Armengol Lopez; Kathleen M. Botham; Charlotte Lawson (International Journal of Vascular Medicine)
Chylomicron remnants (CMRs) contribute directly to human monocyte activation in vitro, by increasing reactive oxygen species (ROS) production and cell migration. In this study, the effects of the oxidative state of CMR on the degree of monocyte activation was investigated. CMR-like particles (CRLPs) were prepared in three different oxidative states, normal (CRLPs), protected from oxidation by incorporation of the antioxidant, probucol (pCRLPs), or oxidised with CuSO4 (oxCRLPs). Lipid accumulation and ROS production were significantly increased in primary human monocytes incubated with CRLPs, whilst secretion on monocyte chemoattractant protein-1 was reduced, but oxCRLPs had no additional effect. In contrast, pCRLPs were taken up by monocytes to a lesser extent and had no significant effect on ROS or MCP-1 secretion. These studies suggest that the oxidative state of CMRs modulates their stimulation of the activation of peripheral blood human monocytes and that dietary antioxidants may provide some protection against these atherogenic effects.